2019
DOI: 10.1002/humu.23751
|View full text |Cite
|
Sign up to set email alerts
|

D‐2‐hydroxyglutaric aciduria Type I: Functional analysis of D2HGDH missense variants

Abstract: D‐2‐hydroxyglutaric aciduria Type I (D‐2‐HGA Type I), a neurometabolic disorder with a broad clinical spectrum, is caused by recessive variants in the D2HGDH gene encoding D‐2‐hydroxyglutarate dehydrogenase (D‐2‐HGDH). We and others detected 42 potentially pathogenic variants in D2HGDH of which 31 were missense. We developed functional studies to investigate the effect of missense variants on D‐2‐HGDH catalytic activity. Site‐directed mutagenesis was used to introduce 31 missense variants in the pCMV5‐D2HGDH e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…However, as the activity assays were carried out using the cell lysates of HEK293 cells overexpressing the wild-type and mutant D-2-HGDH proteins, the measured activities seem to be inaccurate probably due to inaccurate measurement of the enzyme’s concentration caused by interference of other endogenous proteins. For instance, the activity of wild-type D-2-HGDH was determined to be 1.73 nmol/min/mg 43 , which is 3 orders of magnitude lower than the activity (2.01 μmol/min/mg) determined in this work (Fig. 3a ).…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…However, as the activity assays were carried out using the cell lysates of HEK293 cells overexpressing the wild-type and mutant D-2-HGDH proteins, the measured activities seem to be inaccurate probably due to inaccurate measurement of the enzyme’s concentration caused by interference of other endogenous proteins. For instance, the activity of wild-type D-2-HGDH was determined to be 1.73 nmol/min/mg 43 , which is 3 orders of magnitude lower than the activity (2.01 μmol/min/mg) determined in this work (Fig. 3a ).…”
Section: Resultscontrasting
confidence: 75%
“…Truncated variants are usually deemed as pathogenic, whereas the functional roles of missense variants and their pathogenicity remain elusive. A previous functional study of the missense variants associated with type I D-2-HGA showed that compared to the wild-type D-2-HGDH, 18 mutants have severely impaired activity (<6%) and 13 mutants have substantially reduced activity (17%–94%) 43 . However, as the activity assays were carried out using the cell lysates of HEK293 cells overexpressing the wild-type and mutant D-2-HGDH proteins, the measured activities seem to be inaccurate probably due to inaccurate measurement of the enzyme’s concentration caused by interference of other endogenous proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific degradation of r -2HG to 2OG proceeds via r -2HG-dehydrogenase (EC 1.1.99.39) ( 94 ) localized to the mitochondrial matrix ( 1 ), whereas the s -enantiomer is catalyzed by the cytosolic plus mitochondrial enzyme of EC 1.1.99.2. A deficiency of r -2HG-dehydrogenase causes type-I glutaric academia ( 107 , 129 , 161 ). Since r -2HG-dehydrogenase accepts electrons from electron transfer flavoprotein:ubiquinone oxidoreductase (ETF:QOR) ( 161 ), deficiencies of this oxidoreductase also lead to a similar disease, glutaric acidemia type-II.…”
Section: Metabolism Of 2hgmentioning
confidence: 99%
“…Patients with biallelic L2HGDH variants have exclusive neurological findings of psychomotor retardation, cerebellar ataxia, macrocephaly, and epilepsy [356] . Recessive and rare dominant D2HGDH variants in the chiral configuration enzyme, D-2hydroxyglutarate dehydrogenase induce D-2-hydroglutaric acid to 2-ketoglutarate, and patients present with epilepsy, hypotonia, and psychomotor retardation [357] .…”
Section: Pyruvate Dehydrogenase Complexmentioning
confidence: 99%